Mesothelin-specific CD8+ T Cell Responses Provide Evidence of In Vivo Cross-Priming by Antigen-Presenting Cells in Vaccinated Pancreatic Cancer Patients - Amy Thomas; Lynn M. Santarsiero; Eric R. Lutz; Todd D. Armstrong; Yi-Cheng Chen; Lan-Qing Huang; Daniel A. Laheru; Michael Goggins; Ralph H. Hruban; Elizabeth M. Jaffee (2004)
Tumor-specific CD8+ T cells can potentially be activated by two distinct mechanisms of major histocompatibility complex class I–restricted antigen presentation as follows: direct presentation by tumor cells themselves or indirect presentation by professional antigen-presenting cells (APCs). However, controversy still exists as to whether indirect presentation (the cross-priming mechanism) can contribute to effective in vivo priming of tumor-specific CD8+ T cells that are capable of eradicating cancer in patients. A clinical trial of vaccination with granulocyte macrophage–colony stimulating factor–transduced pancreatic cancer lines was designed to test whether cross-presentation by locally recruited APCs can activate pancreatic tumor-specific CD8+ T cells. Previously, we reported postvaccination delayed-type hypersensitivity (DTH) responses to autologous tumor in 3 out of 14 treated patients. Mesothelin is an antigen demonstrated previously by gene expression profiling to be up-regulated in most pancreatic cancers. We report here the consistent induction of CD8+ T cell responses to multiple HLA-A2, A3, and A24-restricted mesothelin epitopes exclusively in the three patients with vaccine-induced DTH responses. Importantly, neither of the vaccinating pancreatic cancer cell lines expressed HLA-A2, A3, or A24. These results provide the first direct evidence that CD8 T cell responses can be generated via cross-presentation by an immunotherapy approach designed to recruit APCs to the vaccination site.